2019
DOI: 10.1088/1742-6596/1222/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of decommissioning offshore wind farms: Overview of the European experience

Abstract: In the coming years, an important number of offshore wind turbines will reach the end of their initially planned service life. In a wind turbine end-of-life scenario, owners can decide between extending the life of the asset, repowering the site or decommissioning. This decision-making process is affected by important sources of uncertainty, especially in offshore environments. The limited experience makes the decommissioning procedure challenging, as it is still largely unexplored. This work assesses the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 24 publications
0
26
0
4
Order By: Relevance
“…The most practical method of waste management for blades is energy recovery through incineration. Some non-recyclable wastes include lubricants and coolants, power electronics and composite materials (Januário et al 2007;Cherrington et al 2012;Topham et al 2019). The waste management methods for different wind turbine components are presented in Table 3.…”
Section: Waste Managementmentioning
confidence: 99%
“…The most practical method of waste management for blades is energy recovery through incineration. Some non-recyclable wastes include lubricants and coolants, power electronics and composite materials (Januário et al 2007;Cherrington et al 2012;Topham et al 2019). The waste management methods for different wind turbine components are presented in Table 3.…”
Section: Waste Managementmentioning
confidence: 99%
“…(Castro-Santos et al 2016) have performed a detailed cost and feasibility assessment of repowering as an end-of-life scenario for wind farms. Finally, a number of location-specific studies for repowering can be found in the literature (Bezbradica et al 2016;Sun, Gao, and Yang 2019;Topham et al 2019a).…”
Section: Repoweringmentioning
confidence: 99%
“…55 The issues attendant to decommissioning offshore wind farms are complex, 56,57 but the rapid growth in wind energy, in recent years, is likely to become matched by an equivalent rate of dismantlement, and for the technology to be considered as a ‘clean’ energy source, a significant degree of repurposing and recycling, with minimal final disposal of the wind turbine components, is necessary. 58 While existing experience is limited, it seems clear that there are considerable knowledge gaps regarding the various steps involved, and due to the complexity of the offshore environment, and the considerable variation among different wind energy projects, it is vital to have clear procedural plans in place, and to make appropriate risk assessments, in advance of any specific decommissioning programme being undertaken. 58 There is also, currently, a lack of a specific regulatory framework for decommissioning wind farms, which complicates such issues as liabilities, and the drawing up of necessary plans both for the process itself, and in dealing with any consequent environmental impacts.…”
Section: Recycling From Low-carbon Energy Sources: Photovoltaic Modulmentioning
confidence: 99%
“…58 While existing experience is limited, it seems clear that there are considerable knowledge gaps regarding the various steps involved, and due to the complexity of the offshore environment, and the considerable variation among different wind energy projects, it is vital to have clear procedural plans in place, and to make appropriate risk assessments, in advance of any specific decommissioning programme being undertaken. 58 There is also, currently, a lack of a specific regulatory framework for decommissioning wind farms, which complicates such issues as liabilities, and the drawing up of necessary plans both for the process itself, and in dealing with any consequent environmental impacts. 58…”
Section: Recycling From Low-carbon Energy Sources: Photovoltaic Modulmentioning
confidence: 99%
See 1 more Smart Citation